Business Model in Air Transport: Evolution of Innovation Concept - Passaro, Pierluigi (European Scientific Journal, ESJ, 2017)
With the advent of the knowledge society, new opportunities, business models and concepts have emerged in most industrial sectors and in particular in the transport sector. The European air travel market, dominated by airlines, influenced to varying degrees from their countries of origin, has been, since the early nineties, completely revolutionized by the entrance in the competitive arena of several small companies, which, in accordance with the principles of „disruptive innovation‟, have completely changed the field of passenger transport. To understand how this was possible, it is necessary to investigate, just with the help of these new tools of Strategic Management as the business models, about the way in which these airlines are able to generate their business and create value. This work aims to analyse the close relationship between innovation of product / service and corporate business model in order to understand the dynamics of the relationship. Various contributions from literature showed how the concept of innovation within the company has evolved over the years and what were the approaches used to study it. This analysis begins with the study of the contributions of Schumpeter, the first economist to write about innovation and author of the dynamic development model and creator of the first distinction between innovation and invention. His theories have made a major contribution in this area, but none the less were also constructively criticized by other economists such as Freeman, who introduced the concept of incremental innovation and analysed the factors triggering innovation. Albernathy and Clark then added another fundamental element of analysis: the competitive environment. They studied the influence of innovation on those factors that are considered essential to achieve a competitive advantage. The same Albernathy, with Utterback, then studied the dynamics of innovations over time. Each of the cited authors analysed the phenomenon of innovation in a different light and all of their contributions allows for a broad and comprehensive concept. The picture is completed by adding the recent contributions of Christensen, who has taken up and deepened the concepts of "sustaining innovation" and " disruptive innovation" and, especially, began to highlight how essential it is that innovation is supported by a suitable business model. In this regard, he has shown that even the same business model can be object of innovation and that this type of innovation is one of the main drivers of the creation of competitive advantage.